MED12 controls the response to multiple cancer drugs through regulation of TGF-β receptor signaling - Huang, Sidong; Hölzel, Michael; Knijnenburg, Theo; Schlicker, Andreas; Roepman, Paul; McDermott, Ultan; Garnett, Mathew; Grernrum, Wipawadee; Sun, Chong; Prahallad, Anirudh; Groenendijk, Floris H; Mittempergher, Lorenza; et al. (Cell, 2012)
Inhibitors of the ALK and EGF receptor tyrosine kinases provoke dramatic but short-lived responses in lung cancers harboring EML4-ALK translocations or activating mutations of EGFR, respectively. We used a large-scale RNAi screen to identify MED12, a component of the transcriptional MEDIATOR complex that is mutated in cancers, as a determinant of response to ALK and EGFR inhibitors. MED12 is in part cytoplasmic where it negatively regulates TGF-βR2 through physical interaction. MED12 suppression therefore results in activation of TGF-βR signaling, which is both necessary and sufficient for drug resistance. TGF-β signaling causes MEK/ERK activation, and consequently MED12 suppression also confers resistance to MEK and BRAF inhibitors in other cancers. MED12 loss induces an EMT-like phenotype, which is associated with chemotherapy resistance in colon cancer patients and to gefitinib in lung cancer. Inhibition of TGF-βR signaling restores drug responsiveness in MED12(KD) cells, suggesting a strategy to treat drug-resistant tumors that have lost MED12.